Analısıs Pengaruh Kualıtas Makanan, Kualıtas Pelayanan, dan Kualıtas Lıngkungan Fısık Terhadap Mınat Berperılaku dengan Kepuasan Pelanggan Sebagaı Varıabel Medıası Pada Café dı Kota Batam - Robby Kurniawan; Valencia Valencia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The purpose of this study is to analyze the related factors that influence the behavioral intention of customers in cafes in Batam city. This research was conducted on the grounds that the cafe trend is increasing day by day in the people of Batam city so that this research can be useful as a guideline regarding the factors that influence customer behavioral intention for related parties. The sample used in this study amounted to 385 respondents who are residents of the city of Batam, which were obtained through the distribution of online questionnaires on social media. Sampling was carried out by purposive sampling technique and data processing was carried out with the help of Smart PLS (Partial Least Square) 3 software. The results of the analysis of this study prove that the independent variables used such as food quality, service quality, and physical environment quality have a significant positive effect on the mediating variable, namely customer satisfaction and the dependent variable, namely behavioral intention. In addition, the mediating variable, namely customer satisfaction, has also been shown to have a significant positive effect on the dependent variable, namely behavioral intention.